Code Switching in Cooking Show Programs on Youtube - Suprihatin, Yeni; Ninsiana, Widhiya; Septiyana, Linda (Universitas Pendidikan Mandalika, 2024)
This study was inspired by code-switching used by Farah Quinn, an influencer known for her cooking skills and unique communication style, including the use of a variety of languages in her YouTube contents. This is a descriptive qualitative study which technically collected the data through observation, and documentation. The data were then classified to further identify code switching types in Farah Quinn’s in YouTube. The results revealed that three types of code switching, intra-sentential code-switching, inter-sentential code-switching and tag switching were found Farah Quinn's YouTube videos. The speaker’s language use contains the most forms of code switching as referred to Hoffman's theory such as intra-sentential code switching appeared as many as 121 use with 73%, inter-sentential found 36 times with 22%, and the last most frequently appeared was tag switching found 9 times with 5%. Based on the functions. there were 148 quotations appear with 89%, 13 interjections with 8%, and 5 message qualification with 3%. The use of quotations was the first major style of code-switching used purposefully by Farah Quinn to satisfy her linguistic demands or preferences to the audience, making the discourse more inclusive and approachable. Interjections allow Farah Quinn to communicate her emotions or reactions, providing richness and dimension to the speech during the program.